EVALUASI PELAKSANAAN PEMUNGUTAN DAN PROSEDUR PENCATATAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KOTA MANADO - Imon, Alfira Irene; Sabijono, Harijanto; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2017)
Land Tax and Rural and Urban Buildings (PBB-P2) is a new type of tax for regions. The enactment of Law Number 28 Year 2009, then all revenues from UN-P2 are regional rights because the process of data collection, appraisal, determination, administration, collection/collection and service of PBB-P2 is held fully by local government (regency/municipality). The transfer of PBB-P2 management rights to local government is done no later than January 1, 2014. The purpose of this research is to know how the collection and recording procedure of Land and Rural Land and Urban Tax in Manado City. This type of research uses descriptive qualitative analysis method by describing the reality or the state of an object studied that is directly related in this research. The result of the research shows that the implementation of PBB-P2 collecting as local tax in Manado City has been running well and is in accordance with the existing procedures, although there are still shortcomings and obstacles in the implementation of the collection. Based on the accounting records of the Manado Regional Tax and Retribution Board of Manado has been implemented in accordance with Government Regulation No. 71 of 2010, although there is still a journal entry that is not applied because the journal entry is made by depositing income from the treasurer's cash to the local treasury and direct payment to the cash account areas conducted by the taxpayer.Keywords : collection, recording, PBB-P2